2013
DOI: 10.1097/nna.0b013e3182786064
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Authentic Leadership and Empowerment on New-Graduate Nurses’ Perceptions of Interprofessional Collaboration

Abstract: Results suggest that authentic leadership and structural empowerment may promote interprofessional collaborative practice in new nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 26 publications
4
50
0
6
Order By: Relevance
“…There was a positive, and significantly proven, influence of real-life leadership on the structure of empowerment, performance and job satisfaction (11) . Therefore, it was proven that leadership style played a key role in job satisfaction (11) ; and that empowerment is a strategy that can create positive working environments in nursing (12) . The perception of recently graduated staff nurses was also a focus of analysis.…”
Section: Leadership Model Tests (N = 6)mentioning
confidence: 99%
“…There was a positive, and significantly proven, influence of real-life leadership on the structure of empowerment, performance and job satisfaction (11) . Therefore, it was proven that leadership style played a key role in job satisfaction (11) ; and that empowerment is a strategy that can create positive working environments in nursing (12) . The perception of recently graduated staff nurses was also a focus of analysis.…”
Section: Leadership Model Tests (N = 6)mentioning
confidence: 99%
“…In health institutions, nurses act as facilitators in the identification of risks for AE, which is a key element in this process due to their assistance role. As the nurses take their leadership roles with the team, there is evidence of improved care (11) , therefore, they should report, compare and measure the facts and consequences of AE. In addition, the nurses are technically responsible for the nursing staff with their class council, and will respond to potential lawsuits related to the occurrence of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…However, no evidence was found to indicate that work support had a buffering effect on the stress-burnout relationship. In contrast, a study by Laschinger, Wong & Grau [18] pointed to authentic behaviour of nursing leaders as important to nurses' perceptions of structurally empowering conditions in their work environments, regardless of experience level, as a contribution to lower levels of emotional exhaustion and cynicism. This is further supported by Peters, Cant, Sellick et al [16], who suggested that managers have a key role in providing education and training for palliative care nurses to support their personal development and to help reduce the vulnerability and the impact of stress in the workplace.…”
Section: Introductionmentioning
confidence: 85%